Water-Wise Cities and Sustainable Water Systems Concepts, Technologies, and Applications - Fu, Guangtao; Wang, Xiaochang C. (IWA Publishing, 2021)
Building water-wise cities is a pressing need nowadays in both developed and developing countries. This is mainly due to the limitation of the available water resources and aging infrastructure to meet the needs of adapting to social and environmental changes and for urban liveability. This is the first book to provide comprehensive insights into theoretical, systematic, and engineering aspects of water-wise cities with a broad coverage of global issues. The book aims to (1) provide a theoretical framework of water-wise cities and associated sustainable water systems including key concepts and principles, (2) provide a brand-new thinking on the design and management of sustainable urban water systems of various scales towards a paradigm shift under the resource and environmental constraints, and (3) provide a technological perspective with successful case studies of technology selection, integration, and optimization on the "fit-for-purpose" basis.